Effect of Papain Enzyme With Different Dosages in Feed on Growth and Survival Rates of Climbing Perch Fish (Anabas testudineus) in Recirculation System - Haycel Andrea Pratama; Rusliadi Rusliadi; Mulyadi Mulyadi (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
The purpose of this study was to determine the best dose of papain in commercial feed to increase the growth of Climbing perch (Anabas testudineus). The research container used was a black bucket with a round shape with a volume of 100 L with a stocking density of 20 fish/container or 400 fish/m3. This study used an experimental method with a completely randomized design (CRD) with one factorial, five treatments and three replications. The treatment applied was feeding containing papain enzyme with different doses, namely P0= without the addition of papain enzyme, P1= addition of papain enzyme 1.25%/kg feed, P2= addition of papain enzyme 2.25%/kg feed, P3= papain enzyme 3.25%/kg feed and P4= addition of papain enzyme 4.25%/kg feed. The results showed a significant effect (P<0.05) on absolute weight, absolute length, specific growth rate, feed conversion ratio, enzyme activity and there was no significant effect (P>0.05) on the survival rate. The best growth rate was found in treatment P3 with absolute weight value: 4.70±0.18 g, absolute length: 2.0±0.20 cm, specific growth rate: 2.21±0.02% per day, survival: 100 %, feed conversion ratio: 1.26±0.03 %, and number of enzymes: 0.0716±0.0007 IU/mL, and with the growth of the average weight of water spinach 60.08 g and the average length of water spinach 100.4 cm in P1 treatment.